Misidentification of Plasmodium Species by Cross-Reacting Primers and Cerebral Malaria Caused by Plasmodium vivax - Rai, Anoopkrishna; Pinto, Deepak Sebastian; Rai, Praveen; Teerthanath, Srinivas; Karunasagar, Indrani; Adiga, Rama (Journal of Health and Allied Sciences NU, 2023)
Introduction The clinical presentation of a case as cerebral malaria with molecular identification confirming it as Plasmodium vivax underlines the importance of using molecular tools to identify the species and type of malaria. The possibility of the relationship between the complication observed during clinical diagnosis and the multifactorial molecular changes could likely be the reason for terming it cerebral malaria.Methods We report four cases analyzed using the quantitative buffy coat technique followed by classical Giemsa stained thick-film microscopy, and nested polymerase chain reaction for the genus-specific region of Plasmodium targeting 18S rDNA followed by species-specific identification with a different set of primers and products confirmation with sequencing.Results Primers targeting P. knowlesi generated the expected product size of 153 base pairs that, upon sequencing, matched with the P. vivax sequence reflecting the relatedness of the species. Likewise, primers targeting P. ovale generated a 456 product whose sequence matched the P. vivax sequence.Conclusion Infection with P. vivax can potentially cause cerebral malaria, and P. vivax can cause severe malaria complications alone or mixed with other species and can show cerebral malaria signs, which are typically associated with P. falciparum infections. The sequence relatedness reflects the genome similarity between P. knowlesi and P. ovale with P. vivax. The need to reconfirm with an additional set of newly reported primers is mandatory.
Keywords: Plasmodium knowlesi; P. falciparum; TFM; QBC; PCR